Amyloid Precursor Protein Regulates Ca(v)1.2 L-type Calcium Channel Levels and Function to Influence GABAergic Short-Term Plasticity - Yang, Li (Society for Neuroscience, 2009)
Amyloid precursor protein (APP) has been strongly implicated in the pathogenesis of Alzheimer's disease (AD). Although impaired synaptic function is believed to be an early and causative event in AD, how APP physiologically regulates synaptic properties remains poorly understood. Here, we report a critical role for APP in the regulation of L-type calcium channels (LTCC) in GABAergic inhibitory neurons in striatum and hippocampus. APP deletion in mice leads to an increase in the levels of Ca(v)1.2, the pore-forming subunit of LTCCs, and subsequent increases in GABAergic calcium currents (I(Ca(2+))) that can be reversed by reintroduction of APP. Upregulated levels of Ca(v)1.2 result in reduced GABAergic paired-pulse inhibition and increased GABAergic post-tetanic potentiation in both striatal and hippocampal neurons, indicating that APP modulates synaptic properties of GABAergic neurons by regulating Ca(v)1.2. Furthermore, APP physically interacts with Ca(v)1.2, suggesting a mechanism in which loss of APP leads to an inappropriate accumulation and aberrant activity of Ca(v)1.2. These results provide a direct link between APP and calcium signaling and might help explain how altered APP regulation leads to changes in synaptic function that occur with AD.